2017
DOI: 10.1037/int0000031
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy training: A comparative qualitative study on motivational factors and personal background of psychodynamic and cognitive behavioural psychotherapy candidates.

Abstract: Therapist variables have received growing attention in the context of psychotherapy research. The presented study aims at expanding the knowledge about professional development by examining motives of career choice and choice of therapeutic orientation in psychotherapy candidates. Twenty-four master's-level psychologists, who had just begun either a cognitive-behavioral (CBT; n ϭ 12, all female, mean age 29.4 years) or psychodynamic (PDT; n ϭ 12, 8 female, 4 male, mean age 31.8 years) therapy training program,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…This cluster is mainly motivated by personal interests and attributes higher relevance to the features of the theoretical approach, without accurately examining the quality of training offer, the prestige of the school or teachers and further school/training related specificities. This result seems to be consistent with the study by Safi et al (2017), who found that candidates for psychodynamic psychotherapy training emphasize the role of personal experiences, interest in self-exploration and life history background in their decision for the respective therapeutic orientation, as well as the importance of working on themselves (Messina et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This cluster is mainly motivated by personal interests and attributes higher relevance to the features of the theoretical approach, without accurately examining the quality of training offer, the prestige of the school or teachers and further school/training related specificities. This result seems to be consistent with the study by Safi et al (2017), who found that candidates for psychodynamic psychotherapy training emphasize the role of personal experiences, interest in self-exploration and life history background in their decision for the respective therapeutic orientation, as well as the importance of working on themselves (Messina et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…From participants' perspective, the ideal psychotherapy school/institution should provide trainees with more clinical practice, be cheap and characterized by a high quality of the training offer, thus suggesting the prominence of the cost-benefit logic. This is confirmed by the study by Safi et al (2017), which has highlighted the importance of financial and time conditions concerning the training, as well as the need for better socioeconomic status and financial security, as factors influencing the decision to undertake psychotherapy training. Concerning job expectations after the completion of psychotherapy training, only 47 % of respondents report (potential or actual) satisfaction (29 %) or dissatisfaction (18 %) about psychotherapy training.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…ESTs often appeal to the trainee's wish to do something and to have clear expectations about what should transpire in the room with a patient. Manualized ESTs hold a particularly salient appeal for practitioners who are more inclined to minimize risk and ambiguity (Safi et al, ).…”
Section: How Do Ests Mitigate Therapist Anxieties?mentioning
confidence: 99%